1‐Hexene Polymerization over Supported Titanium–Magnesium Catalyst: The Effect of Composition of the Catalytic System and Polymerization Conditions on Temperature Dependence of the Polymerization Rate. Issue 1 (28th November 2017) - Echevskaya, Ludmila; Zakharov, Vladimir; Matsko, Mikhail; Nikolaeva, Marina
Abstract: The effect of temperature on the rate of 1‐hexene polymerization over supported titanium–magnesium catalyst of composition TiCl4 /D1 /MgCl2 + AlR3 /D2 (D1 is dibutyl phthalate, D2 is propyltrimethoxysilane, and AlR3 is an organoaluminum cocatalyst) is studied. The unusual data that the polymer rate decreases when temperature is increased from 30 to 70 °C are obtained. The 1‐hexene polymerization rate and the pattern of changes in polymerization rate with temperature depend on a combination of factors such as cocatalyst (AlEt3 or Al( i ‐Bu)3 ) and presence/absence of hydrogen and an external donor in the reaction mixture. These factors differ in their effects on catalytic activity at different polymerization temperatures, so the temperature coefficient ( E eff ) values calculated using the Arrhenius dependence of the polymerization rate on polymerization temperature vary greatly. The "normal" Arrhenius plot where polymerization rate increases with temperature is observed only for polymerization with the Al( i ‐Bu)3 cocatalyst in the presence of hydrogen and without an external donor. Formation of high‐molecular‐weight polyhexene at low polymerization temperatures results in catalyst particle fragmentation, which may additionally contribute to the increase in polymerization rate as polymerization temperature is reduced. Abstract : The unusual data that the polymer rate decreases when temperature is increased are obtained for 1‐hexene polymerization over supported titanium–magnesium catalyst. The calculated effective activation energy values vary within a broad range from –5.5 to 4.8 kcal mol −1 and depend on cocatalyst composition, presence or absence of hydrogen, and external donor. The possible reasons of such phenomenon are discussed.